IMPROVING STUDENTS VOCABULARY BY USING BACK TO THE BOARD GAME AT NINTH GRADE OF ISLAMIC JUNIOR HIGH SCHOOL NURUL YAQIN BANYUATES SAMPANG - Abdul Malik (Universitas Madura, 2019)
The research focuses on some specifics problems; the researcher formulates the research problem are: (1) How is the implementation of back to the board game which can improve the students’ vocabulary at ninth grade of Islamic junior high school NURUL YAQIN Banyuates Sampang in Academic year 2018/2019? (2) How is the improvement of the students’ vocabulary by back to the board game at ninth grade of Islamic junior high school NURUL YAQIN Banyuates Sampang in Academic year 2018/2019? The researcher uses classroom action research. Classroom action research is aimed to reveal the students’ real problem in a classroom. The researcher takes the data from class A of ninth grade students of SMPI Nurul Yaqin Banyuates sampang. In the pre-test there were 5 students from 19 students who passed the KKM. And in the post test 1) there were 10 students who passed the KKM from 19 students, and in the post test 2) there were 15 students who passed the KKM. There were improvement of post test 1 and post test 2. The cycle will be successful if 80 % students get minimum score of 70. After calculating the pre-test and post-test score, it showed that the mean score of pre-test 45,74 and the mean of post-test 74,95. So the researcher didn’t need the next cycle because based on the result of test, the result score that 15 students have reached the minimum criteria